Morin Inhibits Proliferation of SW480 Colorectal Cancer Cells by Inducing Apoptosis Mediated by Reactive Oxygen Species Formation and Uncoupling of Warburg Effect - Sithara, Thomas; Arun, K. B.; Syama, H. P.; Reshmitha, T. R.; Nisha, P. (Frontiers in Pharmacology, 2017)
The study under investigation focuses on in vitro antiproliferative efficacy of the flavonoid morin and the mechanisms by which it inhibits the growth of colon cancer using SW480 colon cancer cells with emphasis on Warburg effect. It was found that the cell proliferation was significantly inhibited by morin in a dose and time dependent manner. Morin induced apoptosis that was correlated with increased levels of reactive oxygen species formation and loss of mitochondrial membrane potential of the cells. In addition, an increase in cleaved PARP, cleaved caspase 3, cleaved caspase 8, cleaved caspase 9 and Bax as well as a decrease in Bcl 2 was observed, indicating morin is inducing both intrinsic as well as extrinsic pathway of apoptosis. This was further confirmed by using downstream caspase 3 inhibitor which indicated that caspase 3 inhibition reduces morin induced cell death. Moreover, the impact of morin on over all energy status when determined in terms of total cellular ATP level showed a decline with low level of glucose uptake and Glut1 expression. The results indicate that morin exerts antiproliferative activity by inducing apoptosis and by reducing Warburg effect in the evaluated cell lines and provide preliminary evidence for its anticancer activity.